Cross sections, stopping powers, and energy loss rates for rotational and phonon excitation processes in liquid water by electron impact. (March 2015) - Kai, Takeshi; Yokoya, Akinari; Ukai, Masatoshi; Watanabe, Ritsuko
Abstract: We calculated cross sections, stopping powers, and energy loss rates for rotational and phonon-mode excitations caused by the impact of an electron in an energy region from 0.1 meV to 100 eV injected into liquid water. The spatial distribution of the decelerated electron depends on these cross sections. We performed calculations assuming an optical approximation with the dielectric functions that are experimentally reported in the literature. We observed that the cross sections lie below 1×10 −16  cm 2 over the considered energy region. The values for rotational excitation processes in the liquid phase are less by three orders of magnitude than those in the gas phase because of the screening effect of neighboring water molecules on the interaction between the incident electron and water molecules. These results suggest that the cross sections in the liquid phase are significantly different from those in the gas phase. The values for phonon-mode excitations in the liquid phase are close to those reported for amorphous ice. Furthermore, we observed that the stopping power shows a maximum around 200 meV, and the energy loss rates, which are derived from the stopping power, depend significantly on the electron energy, particularly below 1 eV. The values obtained here will allow us to precisely estimate the decelerating process of an electron in liquid water to predict radiation effects such as chemical processes in water radiolysis or biomolecular damage induction strongly involved in low energy electron processes. Highlights: Cross sections in liquid water by electron impact of low energy were calculated. Rotational cross section in liquid phase are much less than those in gas phase. Energy loss rates depend significantly on the electron energy below 1 eV.